Implementasi Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Motivasi Belajar Akuntansi Siswa Kelas X Akuntansi - Belleantari, Nanda (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to assess the implementation of the Think Pair Share (TPS) type cooperative learning model to increase motivation to learn accounting in students in class X Accounting. The TPS model consists of three steps, namely Think, Pair, and Share, which can stimulate student interaction and active participation in learning. The problem faced is the low motivation of students to learn in accounting, which can be seen from their lack of involvement in learning. Therefore, the application of the TPS model is expected to increase student motivation and learning outcomes. This research method uses literature studies on scientific articles, textbooks, and research journals on cooperative learning and learning motivation. The data collection process is carried out by looking for validated and reliable sources of literature, as well as making selections to ensure the quality of the data used in the research. The results showed that after applying the TPS model, there was a significant increase in student learning motivation. Students become more active in group discussions, more enthusiastic in understanding the material, and show improved learning outcomes. In conclusion, the TPS model has proven to be effective in increasing student learning motivation and can be applied to improve the accounting learning process